Case of Transient Osteoporosis of the Hip in Pregnancy - Hamza Sucuoğlu; Sermed Hussain; Şansın Tüzün (Galenos Yayinevi, 2014)
Transient osteoporosis of the hip is an uncommon disease, the cause is not known. It is usually seen in women in the third trimester of pregnancy and in middle-aged men. Patients present with acute, severe hip pain which generally resulting in gait disorder. Prognosis of transient osteoporosis of the hip is good. Within few months of appropriate conservative aproach and bed rest patient's complains can be fully recovered. In this article; we present the clinical features, diagnosis and treatment options of patients presented to our clinic with severe bilateral hip pain during the third trimester of pregnancy diagnosed as transient osteoporosis accompanied by literature review.